Democratic Practices in Bangladesh - K.C., Khadga (Tribhuvan University Journal, 2016)
Unless Bangladesh will find credible means to change the political culture within which it function, the viability of democracy will remain doubtful. Though it is about four decades of independence, the history of democracy isn’t worth to value its principles in its actual practice. Bangladesh’s democracy is distorted by the malpractices of political power by her politicians. The quality of democracy in the country has been jeopardized by the immature practices and attitudes by its political party, in or out of power. In fact, the democracy in Bangladesh is deprived within/by the practice of democracy itself. Consequently, democracy becomes fragile and cannot run smoothly with its own spirit. It is now widely accepted that Bangladesh is facing a crisis of governance which originates in malfunctioning of the democratic process. The qualitative deterioration of governance leads to raise lack of concern in pursuing democratic values in practice. The people of this country cannot extract favors from democracy rather their interests become somewhat distorted. In this way the steady failure to get better governance could threaten the sustainability of practicing democracy in Bangladesh repeatedly.